Design of differentially-driven chip antenna - Tan, Heng Chuan. (2011)
In this thesis, a differentially driven microstrip antenna using an aperture coupled feed technique is proposed. A differential antenna is preferred because of lower noise; lower susceptibility to interference and is more suitable for high level integration or single chip solution of radio systems. Thus, the use of lossy balun which is often used to connect single-ended antenna to RF circuits can be eliminated.